IMPORTANT INFORMATION-ANALYTICAL METHODS FOR ASSESSING THE RISK OF ACCIDENTS IN TRAFFIC - Dilshod Imamaliev; Alisher Kholikov; Asem Kaipova (Modern American Journals, 2025)
This article publishes the results of a study on the information and analytical assessment of the risk of accidents in road traffic in the Republic of Uzbekistan. As part of the study, an integrated approach was implemented to consider the problem of road accidents from various points of view and take into account the views of all interested parties. The research methodology included both qualitative and quantitative analyses. Particular attention is paid to the development of recommendations aimed at minimizing the risks associated with the human factor, the technical condition of cars, the characteristics of the road infrastructure and the influence of the environment. The use of the Smeed method made it possible to determine the relationship between the level of social and transport risks, which helped to identify the real situation in traffic that required increased attention. Using the Q-Cochran method, the opinions of drivers were systematized, which helped highlight the subjective aspects of risk factor perception, including dangerous manoeuvres, speeding and lack of visibility on the roads.
Keywords: Traffic, Road accidents, Road injuries, Smeed’s method, Q-test Cochran’s, Manchester Driver Questionnaire, Analytical hierarchy method, Expert panel, Road safety audit.